Analysis of the Mental Workload Associated With the Use of Virtual Reality Technology as Support in the Higher Educational Model - Santiago Criollo-C; Jose Enrique Cerezo Uzcategui; Andrea Guerrero-Arias; Agariadne Dwinggo Samala; Soha Rawas; Sergio Lujan-Mora (IEEE Access)
In recent years, the continuous development of digital technologies has expanded the possibilities for their application in the educational environment, allowing to improve the learning experience by making it more interactive, visually appealing, and accessible to different learning styles. The use of technologies, such as augmented reality (AR) and virtual reality (VR), is transforming the educational model, offering more immersive, personalized, and effective educational experiences for students. Nevertheless, it is essential to consider the mental workload that students may experience when using immersive technologies. This load can manifest itself as difficulty in understanding concepts, frustration, cognitive effort, time demands, among others. Therefore, mental workload of immersive educational experiences must be addressed, as it can negatively affect the learning experience for students. If students experience feelings of overwhelm or frustration, they are less likely to retain information and improve their learning. There is currently research on how to design user interfaces in VR applications to reduce mental workload. This includes the use of user-centered design techniques and the implementation of more intuitive interaction strategies. Nevertheless, the research presented in this paper is not only focused on the appropriate development of a VR application to support the educational model, but also on the analysis of the mental load perceived by students. For this purpose, the NASA-Task Load Index (TLX) tool was used in a group of volunteer students from a university in Ecuador. The main findings are encouraging and show that the mental load experienced by students is relatively low. However, to mitigate the mental workload associated with the use of immersive technologies, it is important to design educational experiences to be intuitive, easy to use and not overload the student with unnecessary information. Furthermore, it is essential to incorporate rest periods and restrict continuous use to avoid mental fatigue.